The significance of solo singing on the wellbeing of Finnish singing majors - Ong Tan, Kendrich Graemer (2018)
Singing plays an important role in a vocal musician’s wellbeing. Literature on singing training focuses more on the prevalence of performance anxiety and voice science. On the other hand, therapy case studies often do not include assessments specific to the voice and singing. Focusing on MPA of singers may overlook aspects of singing that are as pertinent in therapy. The present study aimed to explore the feelings and attitudes of Finnish singing majors towards solo singing, which may need to be addressed in therapy. Four validated Likert questionnaires relating to perceptions of singing from the fields of psychology and voice medicine were compiled to assess vocal musicians’ perspectives more thoroughly. Invitations were sent to the 8 Polytechnic universities in Finland offering the degree Musiikkipedagogi AMK. Thirty students responded to the survey. Comparison of means and correlations were performed and discussed. Intrinsic and identified motivations correlated with the perceived psychological benefits from singing and vocal image. Perceived vocal fatigue correlated with vocal image. Further investigations may elucidate the positive and negative aspects of solo singing in the Finnish culture. Standardized questionnaires specific to singing revealed the involvement of vocal function and vocal image in a trained singer’s wellbeing state. Further studies are warranted to formulate an extensive questionnaire suitable for solo singers undergoing therapy.